Celebrating research contributions from Australia: Marking the XXIVth annual meeting of the Eating Disorder Research Society. Issue 9 (30th September 2018) - Wade, Tracey
Abstract: This Virtual Issue of the International Journal of Eating Disorders (IJED) is released to mark the XXIVth Eating Disorder Research Society (EDRS) meeting in Sydney, Australia. This is the second EDRS meeting in Australia, reflecting the strong contribution of Australian researchers to eating disorder research internationally. Attendees at the Sydney EDRS meeting will be able to access the top 10 cited papers from IJED by Australian authors in 2016–2017, cited an average of 10.2 times each. It is pleasing to note the strong representation of early career researchers and the range of topics addressed.